Analyzing public procurement process operational inefficiencies in Bangladesh: a study on Department Of Public Health Engineering (DPHE) - Parvez, Md. Zahid (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.